Highlighting sex dimorphism in the molecular mechanisms responsible for sarcopenia in a murine model of liver fibrosis. (March 2023) - Sayaf, K.; Zanotto, I.; Gabbia, D.; Gherardi, G.; Rizzuto, R.; De Martin, S.; Russo, F.P.
Abstract : Introduction: Sarcopenia is present in about 25-70% of patients with chronic liver diseases (CLDs), with higher rates in males. Understanding the mechanisms of CLD-related sarcopenia is mandatory for its management. Aim: We investigated the mechanism of sarcopenia in a murine model of liver fibrosis, focusing on sex-related differences, as well as the mechanisms involved in its resolution during liver regeneration. Materials and Methods: Liver fibrosis was induced in female and male mice by injecting increasing doses of carbon tetrachloride (CCl4, from 0.17 to 0.72 mL/Kg*bw) for 12 weeks. Muscle function and strength were evaluated by the grid hanging and the grip strength test. Mice were sacrificed after 6 and 12 weeks of CCl4 -treatment, and after the 8-week washout period to study regeneration. H&E staining was used to calculate the cross-sectional area (CSA) of muscle quadriceps fibers. Muscle pAkt and p4EBP1 protein expression was assessed by western blot, mRNA expression of Musa, Atrogin-1, Murf-1, and Bnip3 by qRT-PCR. Results: Liver fibrosis was associated to a progressive loss of muscle strength in both sexes as demonstrated by the statistically significant reduction of CSA. pAkt and p4EBP1 levels, promoters of muscle protein synthesis, were not affected by fibrosis development. However, autophagy-related genes (Musa, Atrogin-1, Murf-1, and Bnip3), responsible for the breakdown of muscle proteins, were significantly upregulated in fibrotic mice with respect to controls, especially in females (p<0.05). After the washout period, males recovered muscle strength and CSA, although liver fibrosis was still present, whereas females were characterized by an amelioration of liver histology, not accompanied by a recovery of the muscle function. Conclusion: Sarcopenia is differently affected by CLD in males and females and is not correlated to the degree of liver fibrosis. Muscle atrophy, due to an increase of protein degradation, is more evident and persistent in females than in males.